Mutation in Irf8 Gene (Irf8R294C) Impairs Type I IFN-Mediated Antiviral Immune Response by Murine pDCs - Das, Annesa; Chauhan, Kuldeep Singh; Kumar, Himanshu; Tailor, Prafullakumar (Frontiers in Immunology, 2021)
Plasmacytoid dendritic cells (pDCs) are the key producers of type I interferons (IFNs), thus playing a central role in initiating antiviral immune response. Besides robust type I IFN production, pDCs also act as antigen presenting cells post immunogenic stimulation. Transcription factor Irf8 is indispensable for the development of both pDC and cDC1 subset. However, the mechanism underlying the differential regulation by IRF8 in cDC1- and pDC-specific genomic architecture of developmental pathways still remains to be fully elucidated. Previous studies indicated that the Irf8R294C mutation specifically abrogates development of cDC1 without affecting that of pDC. In the present study using RNA-seq based approach, we have found that though the point mutation Irf8R294C did not affect pDC development, it led to defective type I IFN production, thus resulting in inefficient antiviral response. This observation unraveled the distinctive roles of IRF8 in these two subpopulations—regulating the development of cDC1 whereas modulating the functionality of pDCs without affecting development. We have reported here that Irf8R294C mutation also caused defect in production of ISGs as well as defective upregulation of costimulatory molecules in pDCs in response to NDV infection (or CpG stimulation). Through in vivo studies, we demonstrated that abrogation of type I IFN production was concomitant with reduced upregulation of costimulatory molecules in pDCs and increased NDV burden in IRF8R294C mice in comparison with wild type, indicating inefficient viral clearance. Further, we have also shown that Irf8R294C mutation abolished the activation of type I IFN promoter by IRF8, justifying the low level of type I IFN production. Taken together, our study signifies that the single point mutation in Irf8, Irf8R294C severely compromised type I IFN-mediated immune response by murine pDCs, thereby causing impairment in antiviral immunity.